An UV‐curable epoxy acrylate oligomer with high refractive index containing fluorene: Preparation, characterization, and application. Issue 33 (20th May 2015) - Chen, Jia; Zhou, Yuming; Ding, Qinghua; He, Man
ABSTRACT In this article, a novel UV‐curable epoxy acrylate oligomer (BPEFPGMA) with high refractive index is successfully prepared through semi‐esterification reaction of 9, 9‐bis[4‐(2‐hydroxyethoxy)phenyl]fluorene and phthalic anhydride, followed by end‐caping of glycidyl methacrylate. After 15 times' repetitions, the process and properties of this oligomer are stable and reliable. The resulting BPEFPGMA exhibited low solvent content (≤1600 ppm), low viscosity (1900–2500 mPa s at 60°C), high refractive index (1.587 ± 0.003 at 20°C), and normal Mw (2550–3536 g/mol). The coating formulations of 1.57 UV‐curable glue are mixed with BPEFPGMA as reactive oligomer. Through the technology of UV‐curing forming, the corresponding brightness enhancement films are obtained. The resulting films exhibit normal structure, excellent adhesion (5B), good scratch resistance (50 g), and good abrasion resistance (50 g). They show excellent performance, and have reached the quality standard for use in liquid crystal display industry. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42386.